Efficacy and safety of everolimus plus exemestane in patients with hormone receptor-positive, HER-2-negative advanced breast cancer: Results from the open-label, multicentre, non-interventional BRAWO study - Lüftner, Diana; Schuetz, Florian; Schneeweiss, Andreas; Hartkopf, Andreas; Bloch, Wilhelm; Decker, Thomas; Uleer, Christoph; Stötzer, Oliver; Foerster, Frank; Schmidt, Marcus; Mundhenke, Christoph; Tesch, Hans; et al. (International Journal of Cancer, 2024)
BRAWO, a real-world study, assessed the efficacy, quality of life (QoL) and safety of EVE + EXE in postmenopausal women with HR+/HER2– advanced breast cancer (ABC) in routine clinical practice. Postmenopausal women with HR+/HER2-ABC with recurrence or progression after a NSAI were included. Primary Observation parameters included the evaluation of the effectiveness of EVE + EXE. A multivariate-analysis using Cox proportional hazard model was built to identify predictors of progression. Overall, 2100 patients were enrolled (August 2012–December 2017); 2074 were evaluable for efficacy and safety analyses. Majority of patients (60.6%) received EVE + EXE as first (28.7%) or second-line (31.9%) therapy. Visceral metastases were present in 54.1% patients. Median progression-free survival (mPFS) reported as 6.6 months (95%CI: 6.3–7.0). Multivariate-analysis in a subset of patients (n = 1837) found higher body mass index (BMI) and non-visceral metastases to be independent predictors of favorable PFS. Patients with a BMI of 20 to <25 had a mPFS of 6.0 (95%CI: 5.4–6.4) and those with a BMI ≥30 had mPFS of 8.5 (95%CI: 6.9–9.9). 41.2% patients achieved stable disease and 7.3% partial response. No major changes were observed QoL; 86.4% patients received stomatitis prophylaxis and 41.4% experienced EVE related AEs of stomatitis, mainly low grade. AEs occurred in 91.2% of patients, of which stomatitis (42.6%) and fatigue (19.8%) were most frequent. The BRAWO study provides real-world evidence of efficacy and safety of EVE + EXE in patients with HR+, HER2− ABC. A high BMI and the absence of visceral metastases were independent predictors of PFS in this cohort of patients.
CRIS-Team Scopus Importer:2024-05-10
Keywords: advanced breast cancer; everolimus; exemestane; HER2–; HR+